A Muslim Theory of Human Society: an Investigation into the Sociological Thought of Malik Bennabi by Mohamed Tahir El-Mesawi, (Kuala Lampur, Malaysia, Thinker's Library, 1998, 177 pp.) (American Journal of Islam and Society, 2000)
l11e book is composed of an introduction, five chapters, a bibliography, andan index. In the first chapter, the author presents Malik Bennabi's understandingof religion and its pace in human life. The second chapter outlines his viewsas to why human beings associate with each other and form societies. The thirdchapter deals with the constitution and dynamics of society as conceived byBennabi. The fourth chapter is devoted to culture which features prominentlyin his writings. The final chapter discusses his cyclical theory of human socioculturaland historical development.The author informs us that he was introduced to Bennabi's thoughts by readinghis Le Phenomene Coranique (The Qur'anic Phenomenon). He was soimpressed with Bennabi's writing that when he contributed an article on theprospects of an Islamic theory of human society, he referred not only to theworks of Ali Shariati, Muhammad Baqir as-Sadr, Murtaza Mutahhari, but alsoto Bennabi. An international seminar on Malik Bennabi held at the Universityof Malaya in Kuala Lumpur in 1991 gave him the opportunity to read a paperdealing with Bennabi's contribution to social theory, in addition to inspiring ...